1985
DOI: 10.1128/aem.49.5.1154-1161.1985
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and molecular cloning of cryptic plasmids isolated from Lactobacillus casei

Abstract: Four small cryptic plasmids were isolated from Lactobacillus casei strains, and restriction endonuclease maps of these plasmids were constructed. Three of the small plasmids (pLZ18C, pLZ19E, and pLZ19F1; 6.4, 4.9, and 4.8 kilobase pairs, respectively) were cloned into Escherichia coli K-12 by using pBR322, pACYC184, and pUC8 as vectors. Two of the plasmids, pLZ18C and pLZ19E, were also cloned into Streptococcus sanguis by using pVA1 as the vector. Hybridization by using nick-translated cloned 32P-labeled L. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The restriction map of plasmid pLc2, which is depicted in Fig. 3, did not reveal any structural similarities to previously described plasmids from lactobacilli [8,9,13,20,21]. Cloning of plasmid pLc2 in Escherichia coli was accomplished with vector pRV50, a pBR322 derivative with the chloramphenicol resistance gene of pC194 [22].…”
Section: Cloning Of Plasmid Plc2mentioning
confidence: 94%
See 1 more Smart Citation
“…The restriction map of plasmid pLc2, which is depicted in Fig. 3, did not reveal any structural similarities to previously described plasmids from lactobacilli [8,9,13,20,21]. Cloning of plasmid pLc2 in Escherichia coli was accomplished with vector pRV50, a pBR322 derivative with the chloramphenicol resistance gene of pC194 [22].…”
Section: Cloning Of Plasmid Plc2mentioning
confidence: 94%
“…Plasmid profiles and hybridization with pRV52 of small cryptic plasmids from strains of Lactobacillus curvatus and L. sake. Plasmid DNA of the following strains was analysed: E. coli V517 (1), L. sake DSM20017 (2), L. sake LTH672 (3), L. sake LTH673 (4) L. sake LTH674 (5), L. sake LTH675 (6), L. sake LTH676 (7), L. sake LTH677 (8), L. sake LTH678 (9), L. sake LTH679 (10), L. sake LTH680 (11), L. sake LTH681 (12) L. sake LTH682 (13), L. sake LTH1182 (14), L. sake LTH1650 (15), L. curvatus DSM20010 (16), L. curuatus LTH683 (17), L. curvatus LTH684 (18), L. curvatus LTH685 (19) and L. curvatus LTH686 (20). The plasmid sizes are given in kb.…”
Section: Distribution Of Plc2 Related Plasmids Among Lactobacillimentioning
confidence: 99%
“…While a number of initial descriptive studies have appeared, almost no detailed information is available about plasmid maintainance, compatibility, stability, replication, copy number control and partition in lactobacilli. It is clear that several compatibility groups and replicons must exist in L. casei, since a survey of six strains revealed that some carried multiple plasmids that shared no inter-plasmid DNA-DNA homology [48]. The most detailed molecular analysis of a Lactobacillus plasmid is the report based on sequence analysis, that a plasmid isolated from an L. acidophilus strain encodes divergent promoter-like sequences in a region having high homology to a mini-F-like origin of replication [49].…”
Section: Plasmids In Lactobacillimentioning
confidence: 99%
“…A number of cryptic plasmids isolated from L. casei were cloned into E. coli using pBR322, pUC8, and pACY184 as vectors [48]. The plasmids were also cloned into S. sanguis using pVA-1 (an Em r determining non-conjugal deletion plasmid obtained from pAM/~I).…”
Section: Vectors Constructed From Cryptic Plasmidsmentioning
confidence: 99%
“…Transduction has not been reported for lactobacilli but conjugation [154][155][156] and protoplast fusion [157] have. Cryptic plasmids of Lactobacillus casei have been cloned into E. coli using several vectors [158].…”
Section: Lactobacillusmentioning
confidence: 99%